Utilização do método geoestatístico na avaliação de redes de estações pluviométricas com base na precisão dos resultados de balanço hídrico climatológico - Coutinho, Diego Lemos (2008)
In the management of water resources, agriculture is very representative role, because water is essential should be doing its best use to obtain satisfactory production and high income in accordance with the demands of each culture. The water balance of Thronthwaite-Mather (1955) is a technique of quantification of water availability in soil that is rather used for agricultural planning. Whereas this model lists the physical properties of soil-water with the parameters of entry and exit of water and that the variable of greater influence in the result is the precipitation, there is a need to use information from precipitation with acceptable degree of accuracy, in accordance with the accuracy. To do so, the networks should be tracking very well designed. The geostatistics addition to being an excellent technique for estimation, is a great tool used in the sizing of network monitoring. The combination of these two techniques becomes quite interesting, as well as allowing the knowledge of the spatial water balance with their level of accuracy allows the evaluation of the network of tracking based on the accuracy of water availability. This paper aims at the proposition of methodology for the implementation of these activities. At work, was able to confirm that the precipitation is undoubtedly the variable of greater influence on the results of the water balance and that, to apply the model, the number of stations of the network of tracking temperature may be less. It was also concluded that a network of tracking optimized for the accuracy of estimates of monthly rainfall also offered good measurements based on the accuracy of estimates of water availability less precipitation given by the potential evapotranspiration. Even without the knowledge of its accuracy, the estimated volume of storage of water in the soil calculated for various types of crop / soil type in a specific sub-region, coupled with its spatial analysis, were an interesting tool for agricultural planning and management of water resources, simulate allowing the deployment of diverse cultures, studying its feasibility and ensuring the best use of water.